The impact of COVID-19 pandemic on diagnosis and management of gastrointestinal cancers - Byung Soo Yoo; Ankit Patel; Kevin V. Houston; Alejandra Vargas; Ana Rosa Vilela Sangay; Steve M. D'Souza; David A. Johnson (Open Exploration Publishing Inc., 2023)
Gastrointestinal (GI) cancer is one of the leading causes of death that affect many patients around the world. The coronavirus disease 2019 (COVID-19) pandemic significantly impacted our healthcare system in large that diagnosis and management of GI cancer have suffered with a reduction in cancer screening. This review will describe the current practices of cancer screening during COVID-19 pandemic and summarize how each GI cancer (esophageal, gastric, colorectal, and hepatocellular cancers) has been affected by COVID-19. World widely there has been a decreasing trend in screening, diagnosis, and management of GI cancers during the COVID-19 pandemic. Many healthcare institutions are now observing the effect of this change and implementing practice variations to adapt to the pandemic.